Combined effects of cultivar, culture system, cytokinin type and concentration on in vitro regenerative rate of banana - Silva, Dorival Almeida da; Scherer, Ramon Felipe; Holderbaum, Daniel Ferreira; Guerra, Miguel Pedro; Steiner, Neusa (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2021)
Banana is a major fruit crop of the world. In vitro micropropagation allows for the mass production of propagules of high genetic and sanitary quality; however, that requires continuous protocol improvement, by testing varying conditions of, i.e. in vitro culture system and growth regulator supplementation. This study evaluated the in vitro regenerative rate of banana cultivars SCS451 Catarina (AAB) and SCS452 Corupá (AAA) in different culture systems (permanent immersion (PIS) and intermittent immersion (IIS)) exposed to a range of concentrations (0, 5, 10 and 20 µM) of the cytokinins benzylaminopurine (BAP) and meta-topoline (mT). There were no significant differences between type of cytokinins, but the concentration showed highly significant linear (p<0.001) and quadratic terms (p<0.001), as well as significant interactions with cultivar and culture system. For 'SCS451 Catarina' there were no significant differences between PIS and IIS, but for 'SCS452 Corupá' the highest regenerative rates were observed under IIS (p<0.05). These results indicate that BAP and mT are equally suitable for micropropagation of both tested cultivars, with satisfactory results from 5 to 15 µM. Finally, low cytokinin concentrations (~5 μM) and/or the use of liquid culture medium in IIS may allow for cost reductions in production for both cultivars. Index terms: SCS451 Catarina; SCS452 Corupá; micropropagation; genotype dependence.